The Capital Asset Pricing Model, Inflation, and the Investment Horizon: The Isaeli Experience - Levy, Haim (Journal of Financial and Quantitative Analysis, 1980)
The Capital Asset Pricing Model (CAPM), an equilibrium model for the price determination of risky assets, was developed by Sharpe [16], Lintner [9, 10] and Treynor [21], following the pioneering work of Markowitz [12, 13] and Tobin [20]. In spite of the tremendous impact of this model on the profession, the CAPM still raises many questions, and is inconsistent with a considerable body of empirical evidence.